Quantitative measurement of HER2 expression in breast cancers: comparison with 'real-world' routine HER2 testing in a multicenter Collaborative Biomarker Study and correlation with overall survival. Issue 1 (December 2015) - Yardley, Denise; Kaufman, Peter; Huang, Weidong; Krekow, Lea; Savin, Michael; Lawler, William; Zrada, Stephen; Starr, Alexander; Einhorn, Harvey; Schwartzberg, Lee; Adams, John; Lie, Yolanda; et al.
Abstract Introduction Accurate assessment of HER2 status is critical in determining appropriate therapy for breast cancer patients but the best HER2 testing methodology has yet to be defined. In this study, we compared quantitative HER2 expression by the HERmark™ Breast Cancer Assay (HERmark) with routine HER2 testing by immunohistochemistry (IHC) and fluorescencein situ hybridization (FISH), and correlated HER2 results with overall survival (OS) of breast cancer patients in a multicenter Collaborative Biomarker Study (CBS). Methods Two hundred and thirty-two formalin-fixed, paraffin-embedded breast cancer tissues and local laboratory HER2 testing results were provided by 11 CBS sites. HERmark assay and central laboratory HER2 IHC retesting were retrospectively performed in a blinded fashion. HER2 results by all testing methods were obtained in 192 cases. Results HERmark yielded a continuum of total HER2 expression (H2T) ranging from 0.3 to 403 RF/mm2 (approximately 3 logs). The distribution of H2T levels correlated significantly (P <0.0001) with all routine HER2 testing results. The concordance of positive and negative values (equivocal cases excluded) between HERmark and routine HER2 testing was 84% for local IHC, 96% for central IHC, 85% for local FISH, and 84% for local HER2 status. OS analysis revealed a significant correlation of shorter OS with HER2 positivity by local IHC (HR = 2.6, P = 0.016), central IHC (HR = 3.2, P = 0.015), and HERmark (HR = 5.1, P <0.0001) in this cohort of patients most of whom received no HER2-targeted therapy. The OS curve of discordant low (HER2 positive but H2T low, 10% of all cases) was aligned with concordant negative (HER2 negative and H2T low, HR = 1.9, P = 0.444), but showed a significantly longer OS than concordant positive (HER2 positive and H2T high, HR = 0.31, P = 0.024). Conversely, the OS curve of discordant high (HER2 negative but H2T high, 9% of all cases) was aligned with concordant positive (HR = 0.41, P = 0.105), but showed a significantly shorter OS than concordant negative (HR = 41, P <0.0001). Conclusions Quantitative HER2 measurement by HERmark is highly sensitive, accurately quantifies HER2 protein expression and correlates well with routine HER2 testing. When HERmark and local HER2 results were discordant, HERmark more accurately predicted overall survival.